A Look at the State of Research on [Counter-] Terrorism and Violent Extremism - Schmid, Alex P. (Perspectives on terrorism, 2023)
In continuation of a previous survey published in 2021 in Perspectives on Terrorism, a new survey exploring the state of [counter-]terrorism research, resulted in 50 responses from researchers and directors of think tanks, centres, institutes and programmes in the field of terrorism studies. We had asked them ten topical questions that are both research- and policyorientated, based on suggestions we had earlier received from researchers in the field. The responses to the questionnaire are reproduced in this Research Note in italics, supplemented by our comments on the achievements and challenges presently facing terrorism and violent extremism studies.